The science of motorsport racing - Ferguson, David P. (New York : Routledge, 2018)
Despite its worldwide following, high levels of investment and scientific complexity, there is a lack of evidence-based literature on the science of human performance in motorsport. Focusing on the physiological, psychological and sport medicine aspects of training, performance, injury and safety, The Science of Motorsport is the first book to provide an accessible and up-to-date resource for stakeholders at all levels of motorsport. Addressing the physiological and psychological stresses of racing across a full range of sports, from Formula 1 and IndyCar to NASCAR and endurance racing, the book includes chapters on: nutritional and physical training strategies for drivers; the driver's neck; injury rates and pathologies of open-wheel driving; return to competition from concussion; driver safety; and considerations for pit crews and safety staff. Accessibly written and made up of contributions from world-leading authorities in motorsport science research, this is a crucial resource for racing drivers, physical trainers, pit crew members and safety personnel, as well as researchers and students with an interest in applied sport physiology, applied sport psychology or sport medicine.
The biology of automobile racing, more than just turning left / Lydia Pineault BS and David P. Ferguson -- The physiological stress of automobile racing / Edward S. Potkanowicz -- Nutrition recomendations for race car drivers / Claire Heft Rd and Alexandra Stanjones -- Physical training the neck of the driver athlete / Don Gatherer, Jon Malvern and Angus Perry -- Psychological considerations for motorsport racing / Karl Erickson and Daniel Gould -- Merging medicine and technology to improve safety in motorsports / Terry Trammell, Jeff Horton, and Daniel Colvin -- Return to competition of automobile race car drivers following concussion / Julia Daly -- The safety crew and event staff / Teena M. Garrison and Harish Chander -- Driver and team interactions / David P. Ferguson -- Implementation of the science of automobile racing / Charlie Kimball.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Automobile racing; Sports sciences; GAMES / Gambling / Sports; SPORTS & RECREATION / Business Aspects; SPORTS & RECREATION / Essays; SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; TRAVEL / Special Interest / Sports; SPORTS & RECREATION / General; SPORTS & RECREATION / Motor Sports